2018
DOI: 10.1001/jamaoncol.2018.0104
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Tumor Sequencing as a Replacement for Lynch Syndrome Screening and Current Molecular Tests for Patients With Colorectal Cancer

Abstract: Up-front TS in CRC is simpler and has superior sensitivity to current multitest approaches to LS screening, while simultaneously providing critical information for treatment selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
116
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 36 publications
6
116
1
Order By: Relevance
“…These findings are in line with those reported by other studies, which found Germline testing with a multigene panel should be addressed for all early onset CRCs 46 49. Moreover, Hampel et al suggested tumour sequencing approach as a replacement for current multitest LS screening,50 but these new strategies are not widely available in Iran and are too expensive.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in line with those reported by other studies, which found Germline testing with a multigene panel should be addressed for all early onset CRCs 46 49. Moreover, Hampel et al suggested tumour sequencing approach as a replacement for current multitest LS screening,50 but these new strategies are not widely available in Iran and are too expensive.…”
Section: Discussionsupporting
confidence: 83%
“…Today, cancer genomic‐based precision medicine has led to the use of NGS for universal somatic and germline MMR sequencing for selected‐gene or genome‐wide analysis. This strategy saves the initial step of IHC screening and directly examines the genome; therefore, it may reduce costs if the charge for the genetic test decreases.…”
Section: Discussionmentioning
confidence: 99%
“…51 In tumors with repressed expression of MLH1 and PMS2, further analysis of BRAF mutation or MLH1 promoter methylation is needed to exclude somatic MLH1 alterations, 54 as in case 17 (Table 2). Today, cancer genomic-based precision medicine has led to the use of NGS for universal somatic 55 and germline 19,20 MMR sequencing for selected-gene or genome-wide analysis. This strategy saves the initial step of IHC screening and directly examines the genome; therefore, it may reduce costs if the charge for the genetic test decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of BRAF V600E in the smMIP-based MSI assay streamlines the LS screening pipeline, requiring only one tumour test prior to germline testing of MMR genes, equivalent to tumour-sequencing 22 . We were able to detect low variant allele frequencies in BRAF down to 1.7%, with improved sensitivity compared to HRM analysis, which has an estimated LLoD of 10% 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Next generation sequencing (NGS) of tumours to diagnose MSI have been developed with sensitivities and specificities of >95% 21 . Tumour-sequencing could reduce the recommended LS screening pipeline to two steps (tumour-sequencing and germline confirmation) by simultaneous detection of MSI, BRAF V600E and MMR gene mutations 22 . Coupled tumour and germline-sequencing can also determine the somatic origin of MMR deficiency in 52% of Lynch-like tumours with double somatic MMR mutations, which may avoid unnecessary management of these CRCs as LS 23 .…”
Section: And the National Institute Of Healthmentioning
confidence: 99%